Fragmentation promotes the role of dispersal in determining 10 intermittent headwater stream metacommunities - Gauthier, Maïlys; Launay, Bertrand; Le Goff, Guillaume; Pella, Herve; Douady, Christophe J.; Datry, Thibault (Freshwater biology, 2020)
Dispersal, defined as the movement of individuals among local communities in a landscape, is a central regional determinant of metacommunity dynamics in ecosystems. Whereas both natural and anthropogenic ecosystem fragmentations can limit dispersal, previous attempts to measure such limitations have faced considerable context dependency, due to a combination of spatial extent and associated environmental variability, the wide range of dispersal modes, and abilities of organisms or variation in network topologies. Therefore, the role dispersal plays compared to local environmental filtering in explaining metacommunity dynamics remains unclear in fragmented dendritic ecosystems. We quantified α‐ and β‐diversity components of invertebrate metacommunities across 10 fragmented headwater stream networks and tested the hypothesis that dispersal is the primary determinant of biodiversity organisation in these dynamic and spatially constrained ecosystems. Alpha‐diversity was much lower in intermittent than perennial reaches, even long after rewetting, indicating an overwhelming effect of drying including a legacy effect on local communities. Beta‐diversity was never correlated with environmental distances but predominantly explained by spatial distances accounting for river network fragmentation. The nestedness proportion of β‐diversity was considerable and reflected compositional differences where communities from intermittent reaches were subsets of perennial reaches. Altogether, these results indicate dispersal as the primary process shaping metacommunity dynamics in these 10 headwater stream networks, where local communities recurrently undergo extinction and recolonisation events. This challenges previous conceptual views that local environment filtering is the main driver of headwater stream metacommunities. As river networks become increasingly fragmented due to global change, our results suggest that some freshwater ecosystems currently driven by local environment filtering could gradually become dispersal‐limited. In this perspective, shifts from perennial to intermittent flow regimes represent ecological thresholds that should not be crossed to avoid jeopardising river biodiversity, functional integrity, and the ecosystem services they provide to society.